Desain dan Simulasi Konverter Tiga Fasa AC – DC pada Pico Hydro - Yun Tonce Kusuma Priyanto; Andre Amba Matarru; Muhammad Ridho Dewanto; Rizky Wahyudi (Jurnal Sistim Informasi dan Teknologi, 2023)
Pico hydropower plant is a generator engaged in the field of renewable energy, in general, the power system uses a 3-phase synchronous generator with AC voltage, in its development it can be used as a converter, by converting AC voltage to DC voltage. One of the uses of DC voltage is as so that it can be used as a battery charger or battery discharger. An AC-DC converter, also known as a rectifier, is a device for converting alternating current (AC) to direct current (DC). In general, many technologies in the industrial world utilize converters. In this paper, a simulation design of an AC-DC converter system will be made with a 230 Volt AC input with a DC voltage output. The manufacture of the converter is carried out with different gate values on the thyristors which are simulated using Simulink in MATLAB. The results of this study are in the form of analysis and mathematical calculations of the output of the AC-DC converter where from the simulation results that AC voltage can be converted to DC voltage with the working principle of the thyristor, thus the converter output results can be used in battery chargers and battery dischargers